2006
DOI: 10.1586/14789450.3.3.297
|View full text |Cite
|
Sign up to set email alerts
|

Peptide profiling of cerebrospinal fluid by mass spectrometry

Abstract: The search for biomarkers is driven by the increasing clinical importance of early diagnosis. Reliable biomarkers can also assist in directing therapy, monitoring disease activity and the efficacy of treatment. In addition, the discovery of novel biomarkers might provide clues to the pathogenesis of a disease. The dynamic range of protein concentrations in body fluids exceeds 10 orders of magnitude. These huge differences in concentrations complicate the detection of proteins with low expression levels. Since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…Yet another advantage is the very high sensitivity and reproducibility of FTMS (11), which is higher than that of any other mass spectrometric techniques currently available. In addition, FTMS provides an excellent signal-to-noise ratio because the source of noise in MALDI-FTMS is of physical origin and is not a chemical-based noise as that generated in MALDI-TOF (24). These advantages allow the study of very small numbers of targeted cells.…”
Section: Discussionmentioning
confidence: 99%
“…Yet another advantage is the very high sensitivity and reproducibility of FTMS (11), which is higher than that of any other mass spectrometric techniques currently available. In addition, FTMS provides an excellent signal-to-noise ratio because the source of noise in MALDI-FTMS is of physical origin and is not a chemical-based noise as that generated in MALDI-TOF (24). These advantages allow the study of very small numbers of targeted cells.…”
Section: Discussionmentioning
confidence: 99%
“…Standardized sample handling is also important when trying to compare results between different laboratories (12)(13)(14). In the search for molecular biomarkers related to disorders of the central nervous system, CSF is the most promising biofluid because of its close contact to the affected tissue (13,(15)(16)(17)(18)(19)(20).…”
Section: © 2011 American Association For Clinical Chemistrymentioning
confidence: 99%
“…Furthermore, the general protein concentration in CSF (0.2-0.5 g/l) is much lower than in plasma/serum (60-80 g/l). 22 As most classical biomarkers have been identified among the low-abundant proteins, 23 it is necessary to fractionate and/or deplete the high-abundant circulating proteins that otherwise might mask proteins of low concentrations. It has been shown that fractionation can give up to a tenfold increase in the number of proteins identified.…”
Section: Protein Biomarker Discoverymentioning
confidence: 99%